Essay Review: Evidence-Based Analysis of the COVID Pandemic: COVID: Why Most of What You Know Is Wrong by Sebastian Rushworth - Bauer, Henry (Journal of Scientific Exploration, 2021)
This short book suggests plausible answers to much of what has seemed inexplicable or unbelievable about what governments, the World Health Organization, and popular media have disseminated about the officially declared global pandemic. The author is a recently graduated Swedish physician who recognized even during his training that many of the generally accepted shibboleths about medical matters are not evidence-based; are often, in fact, contrary to the available evidence. Irrespective of his suggestions about COVID, several points in this book are important for everyone to know: Modern medicine focuses on the handling of emergencies but says “extremely little about how to avoid chronic disease and maximize long term health” (p. 7). More than half of the widely accepted recommendations about nutrition are nonsense, without any basis in solid evidence (p. 8): to eat more fruit, fish, vegetables, whole-grain cereals, and less salt, saturated fat, or meat. Much purportedly scientific medical information stems from inappropriate use of surrogate endpoints and improper statistical analyses (pp. 34–39): The usual criterion for statistical significance (p ≤ 0.05) is arbitrary and very weak. The typical marketing ploy of citing relative rather than absolute risks is highly misleading (pp. 40–46). How deadly is COVID?